2015
DOI: 10.1007/s10880-015-9416-9
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Psychosocial Adjustment in Digestive System Cancer

Abstract: The study aims to investigate the contributions of resilience, affective reactions and post traumatic growth (PTG) to psychosocial adjustment and behavioral changes among digestive system cancer patients in Israel. A sample of 200 participants, 57.5 % men (from the 46 to 70-year age range), 1-4 years following diagnosis, completed an inventory assessing demographic and medical information, resilience, current positive affect (PA) and negative affect (NA), PTG, psychosocial adjustment and retrospective report o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 55 publications
1
31
1
7
Order By: Relevance
“…Our results are consistent with previous studies that assessed the association of resilience with stress and well-being measures, psychological distress, and mental health diagnoses. Our findings are supported by the prior studies that have been conducted in various patient groups, including renal transplant recipients [39], patients undergoing hematopoietic stem cell transplant and their relatives [40], patients with cancer [41, 42], patients with head and neck cancer [43], patients with digestive system cancer [4446], trauma patients [47], patients with rare health conditions [48], and patients with spinal cord injury [49].…”
Section: Discussionsupporting
confidence: 88%
“…Our results are consistent with previous studies that assessed the association of resilience with stress and well-being measures, psychological distress, and mental health diagnoses. Our findings are supported by the prior studies that have been conducted in various patient groups, including renal transplant recipients [39], patients undergoing hematopoietic stem cell transplant and their relatives [40], patients with cancer [41, 42], patients with head and neck cancer [43], patients with digestive system cancer [4446], trauma patients [47], patients with rare health conditions [48], and patients with spinal cord injury [49].…”
Section: Discussionsupporting
confidence: 88%
“…Social support refers to assistance provided by other people (family, friends, or others outside a professional support setting), as well as the perception that one is loved, esteemed, and valued by others (144). Evidence suggests a significant link between social support and health, with social support considered an important contributor to improving well-being and reducing distress in cancer patients (16). Family and friends may help cancer patients to process their cancer-related traumatic experiences and may be involved in meaning finding, efforts that could lead to improved interpersonal relationships (26).…”
Section: Factors Determining Resiliencementioning
confidence: 99%
“…Interestingly, despite substantial distress that is associated with a cancer diagnosis and its treatment, many cancer patients manifest remarkable resilience (15, 16). Studies have shown that overcoming cancer and its treatment can be an opportunity for personal growth, as well as for enhanced mental and emotional well-being that could potentially be linked to better coping with disease-related demands (1719).…”
Section: Introductionmentioning
confidence: 99%
“…Resilience was conceptualized broadly as a dynamic process that involves adaptation to stressful conditioning, an adaptation that supports healthy levels of psychological functioning in the face of traumatic circumstances. 27 Extensive literature studies were conducted to investigate the role of resilience during one or more stages of cancer. Molina et al 28 revealed that promoting resilience is a critical element of patient psychosocial care.…”
Section: Resilience Among Cancer Patientsmentioning
confidence: 99%